Visuo-motor attention during object interaction in children with developmental coordination disorder. (May 2021) - Arthur, Tom; Harris, David J.; Allen, Kate; Naylor, Caitlin E.; Wood, Greg; Vine, Sam; Wilson, Mark R.; Tsaneva-Atanasova, Krasimira; Buckingham, Gavin
Abstract: Developmental coordination disorder (DCD) describes a condition of poor motor performance in the absence of intellectual impairment. Despite being one of the most prevalent developmental disorders, little is known about how fundamental visuomotor processes might function in this group. One prevalent idea is children with DCD interact with their environment in a less predictive fashion than typically developing children. A metric of prediction which has not been examined in this group is the degree to which the hands and eyes are coordinated when performing manual tasks. To this end, we examined hand and eye movements during an object lifting task in a group of children with DCD (n = 19) and an age-matched group of children without DCD (n = 39). We observed no differences between the groups in terms of how well they coordinated their hands and eyes when lifting objects, nor in terms of the degree by which the eye led the hand. We thus find no evidence to support the proposition that children with DCD coordinate their hands and eyes in a non-predictive fashion. In a follow-up exploratory analysis we did, however, note differences in fundamental patterns of eye movements between the groups, with children in the DCD group showing some evidence of atypical visual sampling strategies and gaze anchoring behaviours during the task.